Aplicação do controle estatístico para avaliação da capacidade do processo de descontaminação em uma indústria metal mecânica - Souza, Bruno Henrique Pedrolo de (2020)
This work aims to carry out a qualitative study on a new decontamination process, with the aim of guaranteeing and rigorously controlling the quality of the product in production. The aim is to qualify the process within the limits of quality, analyzing the retrospect of the process throughout the study period, using quality tools and capability analysis. With this, the aim is to define the final condition of the process and enable it or not to deliver compliant products. In the end, it was concluded that the process has the capacity to produce with quality assured by the specification and proposing improvements to maintain the state of the process for a future period of analysis.